2001
DOI: 10.1128/aac.45.8.2309-2315.2001
|View full text |Cite
|
Sign up to set email alerts
|

Kappacin, a Novel Antibacterial Peptide from Bovine Milk

Abstract: Caseinomacropeptide (CMP) is a heterogeneous C-terminal fragment (residues 106 to 169) of bovine milk -casein composed of glycosylated and phosphorylated forms of different genetic variants. We have demonstrated that CMP has growth-inhibitory activity against the oral opportunistic pathogens Streptococcus mutans and Porphyromonas gingivalis and against Escherichia coli. CMP was fractionated using reversed-phase highperformance liquid chromatography (RP-HPLC), and each fraction was tested for activity against S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
148
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(151 citation statements)
references
References 28 publications
(32 reference statements)
1
148
0
2
Order By: Relevance
“…Binding of magainin-1 to phospholipid vesicles, where the peptide self-assembles, inserts, and form largely pentameric pores, induces the leakage of cellular material. We speculate that in vivo, the channel formed by DCD-1L functions as a proton channel as suggested for kappacin, an AAMP from bovine milk (9,10). For kappacin it has been proposed that it forms ion channels with a proton influx at acidic pH, which slowly results in bacterial cell death by reducing intracellular pH (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Binding of magainin-1 to phospholipid vesicles, where the peptide self-assembles, inserts, and form largely pentameric pores, induces the leakage of cellular material. We speculate that in vivo, the channel formed by DCD-1L functions as a proton channel as suggested for kappacin, an AAMP from bovine milk (9,10). For kappacin it has been proposed that it forms ion channels with a proton influx at acidic pH, which slowly results in bacterial cell death by reducing intracellular pH (9).…”
Section: Discussionmentioning
confidence: 99%
“…Examples of AAMPs are bovine kappacin, the proenkephalinderived peptides peptide B and enkelytin, maximin H5 from the amphibian Bombina maxima, and lysenins from the earthworm Eisenia fetida (5,(7)(8)(9)(10). It has been suggested that these peptides may synergistically enhance the action of CAMPs or other antimicrobial factors in the first line of defense against microbial infection (11).…”
mentioning
confidence: 99%
“…The genes are organised in a cluster of approximately 250 kB [13,41] and share common transcription regulating elements [41]. The locus is considered to influence milk production traits [8,9,17,22,46] and antibacterial activities of derived peptides [29] may also affect the biological fitness of the offspring. Moreover, casein genes harbour a number of variants with suggested effects concerning traits such as the manufacturing properties of milk [1,35].…”
Section: Introductionmentioning
confidence: 99%
“…However, in contrast to the calcium-sensitive α s1 -, β-, and α s2 -caseins, the κ-casein fraction plays a crucial role in the formation, stabilization, and aggregation of the casein micelles and thus affects the technological (Mariani et al, 1976;Aleandri et al, 1990;Lodes et al, 1996;Falaki et al, 1997) and nutritional properties of milk (Mercier et al, 1973(Mercier et al, , 1976Malkoski et al, 2001). Therefore, the κ-casein gene (CSN3) is unlikely to be completely free of selective constraints (Ward et al, 1997).…”
Section: Introductionmentioning
confidence: 99%